Response of fibre optic long period gratings operating near the phase matching turning point to the deposition of nanostructured coatings. - Cheung, C. S.; Topliss, Stephen M.; James, Stephen W.; Tatam, Ralph P. (Optical Society of America, 2008)
The response of the dual resonant bands of a fibre optic long period grating operating near the phase matching turning point to the deposition of a nanostructured coating is investigated. The dual resonant bands are observed to show a high sensitivity to the thickness of the coating, but with opposite signs. Appropriate design of the device, based on the grating period, the refractive index and thickness of the coating and the fibre composition, can allow the sensitivity of the device to the optical thickness to be optimized. A sensitivity of 1.45 nm / nm is observed experimentally.